Transformations to regenerative food systems—An outline of the FixOurFood project. Issue 1 (12th December 2021) - Doherty, Bob; Bryant, Maria; Denby, Katherine; Fazey, Ioan; Bridle, Sarah; Hawkes, Corinna; Cain, Michelle; Banwart, Steven; Collins, Lisa; Pickett, Kate; Allen, Myles; Ball, Peter; et al.
Abstract: This paper provides an outline of a new interdisciplinary project called FixOurFood, funded through UKRI's 'Transforming UK food systems' programme. FixOurFood aims to transform the Yorkshire food system to a regenerative food system and will work to answer two main questions: (1) What do regenerative food systems look like? (2) How can transformations be enabled so that we can achieve a regenerative food system? To answer these questions, FixOurFood will work with diverse stakeholders to change the Yorkshire food system and use the learning to inform change efforts in other parts of the UK and beyond. Our work will focus on shifting trajectories towards regenerative dynamics in three inter‐related systems of: healthy eating for young children, hybrid food economies and regenerative farming. We do this by a set of action‐orientated interventions in schools and the food economy, metrics, policies and deliverables that can be applied in Yorkshire and across the UK. This article introduces the FixOurFood project and concludes by assessing the potential impact of these interventions and the importance we attach to working with stakeholders in government, business, third sector and civil society.